Evacuation Preparation Equipment for Infant in a Flood Disaster a Case Study in Baleendah, Bandung Regency - Ahmad Rieskha Harseno; Nedina Sari; Andar Bagus Sriwarno (Journal of Industrial Product Design Research and Studies, 2023)
Bandung Regency is one of the areas located on the banks of the Citarum River. Therefore, it risks flooding, especially in the rainy season. One of the flood disaster victims is an infant. When a flood occurs, infants rely on help from adults to survive. Currently, there is no special equipment to support the pre-evacuation and evacuation of the infant during the flood. Based on the abovementioned concerns, a means for evacuation is required so infants can avoid the flood and ease the evacuation. The method used in this design is Human Centered Design through three stages: inspiration, ideation, and implementation. The result of this research is the design of an infant evacuation preparation facility with the concept of a baby crib. This crib functions as a means for evacuating the infant safely and can also be used in daily activities to help with the bathing and lulling of the infant.